The Development of Heyzine Flipbook-Based Interactive E-Book in Arabic Language Learning at Madrasah Aliyah - Febrizka, Karina; Rahmawati, Rahmawati; Hanomi, Hanomi (Abjadia : International Journal of Education, 2026)
The rapid development of digital technology, especially in the world of education, has driven changes in the provision and use of teaching materials, starting from conventional print media to more interactive and easily accessible digital learning resources. This study aims to develop an interactive e-book based on Heyzine Flipbook media. This study uses a development research method with the ADDIE development model. The teacher needs analysis showed a score of 84.4%, for the student needs analysis showed a score of 80.4%, both indicating that teachers and students "strongly agree" to the development of an interactive e-book product based on Heyzine Flipbook media. This product was validated by media experts with a score of 95.5%, material experts with a score of 94.4%, language experts with a score of 90.6%, all three are categorized as "very good" with minor revisions. The effectiveness of e-book use is measured from the results of trials, teacher and student responses. The score obtained from the trial results was 94%, for teacher responses 97.5%, and 86.9% for student responses, all three are categorized as "very good". These findings indicate that the Heyzine Flipbook- based interactive e-book product achieved a very high level of validity and user acceptance, thereby empirically meeting the feasibility criteria for use as a digital learning resource supporting Arabic language learning at the Madrasah Aliyah level. However, this study has not tested the effectiveness of e-book use on the comparative improvement of student learning outcomes, so further research is still needed.